2016
DOI: 10.2147/ndt.s90674
|View full text |Cite
|
Sign up to set email alerts
|

A voxel-based morphometric study of age- and sex-related changes in white matter volume in the normal aging brain

Abstract: ObjectiveTo carry out a cross-sectional study of 187 cognitively normal Chinese adults using the voxel-based morphometry (VBM) approach to delineate age-related changes in the white matter volume of regions of interest in the brain and further analyze their correlation with age.Materials and methodsA total of 187 cognitively normal adults were divided into the young, middle, and old age-groups. Conventional magnetic resonance imaging was performed with the Achieva 3.0 T system. Structural images were processed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 31 publications
(36 reference statements)
2
15
0
Order By: Relevance
“…It is possible that the BREATHE study, in measuring air pollution in late childhood, did not capture the sensitive exposure time windows to explore the effects of TRAP on WM. In contrast, at the other end of the age spectrum, WM volume decreases rapidly from 60 years onwards [ 42 ]. Aging makes the oligodendrocytes more prone to degeneration, resulting in increased myelin breakdown [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the BREATHE study, in measuring air pollution in late childhood, did not capture the sensitive exposure time windows to explore the effects of TRAP on WM. In contrast, at the other end of the age spectrum, WM volume decreases rapidly from 60 years onwards [ 42 ]. Aging makes the oligodendrocytes more prone to degeneration, resulting in increased myelin breakdown [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, WM volume gradually increases in the first 40 years of life, peaks at around 50 years of age, and then decreases rapidly from 60 years of age onwards (Liu et al, 2016). Even with healthy aging, WM lesions (also known as leukoaraiosis) are evident as WM hyperintensities on T2-weighted MRI.…”
Section: White Matter Changes In the Normal Aging Brainsmentioning
confidence: 99%
“…Almost all studies have shown an absence of an interaction between age and gender in WM volume and therefore suggest a lack of gender differences in age-related WM volume loss (Inano et al, 2013; Liu et al, 2016; Ryan et al, 2014). However, the effect of gender on aging-induced loss of WM integrity remains controversial.…”
Section: White Matter Changes In the Normal Aging Brainsmentioning
confidence: 99%
“…Here, the gender was not considered separately for the computational head modeling. Although, there are studies which reported age-related brain changes to vary with gender (Cowell et al, 1994;Ge et al, 2002;Xu et al, 2000) and the male and female cerebellar lobe are different in size (Liu et al, 2016), no gender-specific correlation between cerebellar volume have been reported (Arani et al, 2015;Jäncke et al, 2015). Another limitation of this study is that our MRI age-group data had five years interval.…”
Section: Discussionmentioning
confidence: 79%